Survey on blockchain privacy protection techniques in cryptography - Feng LIU; Jie YANG; Jiayin QI (网络与信息安全学报)
In recent years, the issue of data privacy has attracted increased attention, and how to achieve effective privacy protection in blockchain is a new research hotspot.In view of the current research status and development trend of blockchain in privacy protection, the privacy protection methods of blockchain in transaction address,prophecy machine and smart contract were explained, and the privacy strategies of blockchain in the protection of basic elements were summarized.Based on high-level literature at home and abroad, two types of blockchain cryptographic protection methods and usage scenarios were analyzed, including special cryptographic primitives and post-quantum cryptography.The advantages and disadvantages of seven cryptographic techniques applicable to current blockchain privacy protection were also reviewed, including attribute-based encryption, special data signature, homomorphic encryption, secure multi-party computation, zero-knowledge proofs, and lattice ciphers.It was concluded that the privacy protection of blockchain applications cannot be achieved without cryptographic technology.Meanwhile, the blockchain privacy protection technologies were analyzed in terms of both basic element protection and cryptographic protection.It was concluded that it was difficult to effectively solve the privacy problem only from the application and contract layers of the blockchain, and various cryptographic technologies should be used to complement each other according to different needs and application scenarios.In addition, according to the current development status of blockchain privacy cryptography, the narrative was developed from blockchain basic element protection and cryptography-based protection.From the perspectives of both endogenous basic element security and exogenous cryptographic privacy security, basic element privacy protection should be studied first, followed by an in-depth analysis of cryptographic protection techniques for blockchain privacy.The strengths and weaknesses and the potential value of the privacy handling aspects of the corresponding safeguards should be measured in terms of the development of technology in conjunction with practical applications, while considering the timeliness of the technology.Finally, an outlook on the future direction of blockchain privacy protection technologies was provided, indicating the issues that need to be addressed in focus.